1983
DOI: 10.1111/j.1528-1157.1983.tb04918.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Partial Epileptic Seizures in the Adolescent

Abstract: Actuarial analysis was applied to the notes of 235 patients having a partial seizure for the first time between the ages of 12 and 18 years to establish the best predictive indicators of outcome. Among the factors considered to affect significantly the outcome were the seizure type (elementary or complex symptomatology), the initial EEG, the seizure frequency, the etiological factors, and an association with generalized seizures. Sex, age of onset, and topography of EEG paroxysmal abnormalities had no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

1985
1985
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
1
6
0
3
Order By: Relevance
“…Analogous conclusions were drawn by Sofijanov [15] and Okuma and Kumashiro [16]. On the other hand, a multicen ter Italian study on the prognosis for epilepsy in newly referred patients demonstrated that the risk of developing moderate to severe epi lepsy is higher in patients aged < 10 years at onset [17], Other variables previously reported as as sociated with a worse prognosis, such as a family history of seizures [4] and the presence of epileptic abnormalities in the pretreatment EEG [16,[18][19][20], were assessed and were found not to be helpful in predicting prognos tic factors in our study. Previous papers ad dressing the problem of the EEG findings and the risk of chronic epilepsy did not yield sig nificant results [4,15,17], While a negative association between the prospect for seizure control and the number, frequency or duration of the seizures before therapy has been consistently reported [4,6,17,21], the present study showed a lack of any such association between seizure outcome and the number of seizures before the begin ning of treatment, in agreement with Sillanpaa [6], Therefore, while there is no doubt that the prognosis for seizure control is inversely pro portional to the disease duration, the role of early treatment has not been yet resolved [10].…”
Section: Prognosis Of Childhood Epilepsysupporting
confidence: 51%
“…Analogous conclusions were drawn by Sofijanov [15] and Okuma and Kumashiro [16]. On the other hand, a multicen ter Italian study on the prognosis for epilepsy in newly referred patients demonstrated that the risk of developing moderate to severe epi lepsy is higher in patients aged < 10 years at onset [17], Other variables previously reported as as sociated with a worse prognosis, such as a family history of seizures [4] and the presence of epileptic abnormalities in the pretreatment EEG [16,[18][19][20], were assessed and were found not to be helpful in predicting prognos tic factors in our study. Previous papers ad dressing the problem of the EEG findings and the risk of chronic epilepsy did not yield sig nificant results [4,15,17], While a negative association between the prospect for seizure control and the number, frequency or duration of the seizures before therapy has been consistently reported [4,6,17,21], the present study showed a lack of any such association between seizure outcome and the number of seizures before the begin ning of treatment, in agreement with Sillanpaa [6], Therefore, while there is no doubt that the prognosis for seizure control is inversely pro portional to the disease duration, the role of early treatment has not been yet resolved [10].…”
Section: Prognosis Of Childhood Epilepsysupporting
confidence: 51%
“…Two thirds of the patients had an aura or automatisms. Postictally, 19 patients were lethargic or slept and seven were confused. All patients had CPS only (23 patients) or CPS with secondary generalization (seven patients).…”
mentioning
confidence: 98%
“…Hierbei befanden wir uns in Übereinstimmung mit anderen Publikationen [10.22,42). Im Gegensatz dazu beschrieben Kaliaperumal et al [21) und Loiseau et al [26] das Vorkommen pathologischer Befunde im initialen EEG als ungünstig für den weiteren Epilepsieverlauf. Übereinstimmend mit D'Allesandro et al (8) und Runge (36) hatte die Grundaktivität keine Bedeutung für die Epilepsieprognose.…”
Section: äTiologie Der Epilepsien Und Lokalisation Der Zerebralen Läsunclassified